New Additions to the Fungi of India - D. NAGARAJU*, C. MANOHARACHARY and (Indian Phytopathology, 2016)
A survey of fungi (2012-2014) associated with litter samples collected from selected forest localities of Telangana revealed that Craspedodidymum abigianense, Cryptocoryneum condensatum, Septosporium bulbotrichum, Bactrodesmium linderi form new additions to the fungi of India.